Recent progress in functional materials for electrochemical detection of pesticides: modification strategies, performance, and future challenges - Zheng, Alvin Lim Teik; Teo, Ellie Yi Lih; Hung, Yiu Pang; Md Saad, Juniza; Zamakshshari, Nor Hisam; Chung, Eric Lim Teik; Ahmad Farid, Mohammed Abdillah; Andou, Yoshito (Springer, 2025)
Widespread pesticides use in agriculture has led to significant groundwater and food contamination, posing severe risks to both human health and the environment. Real-time detection of these emerging contaminants remains a formidable challenge. Electrochemical sensors and biosensors have remained a viable technique for overcoming the limits ascribed to their ultra-sensitivity and rapid detection times as well as excellent sensitivity, reliability, and selectivity. This comprehensive review will encompass the most recent advancements in the utilization of functional materials such as metal–organic framework, MXene, carbon organic framework, carbon nanotubes, and graphene modifiers for the detection of a myriad of pesticides via electrochemical detection techniques, electrode materials, electrolyte solutions, and sample matrices. This review compiles performance data, including detection limits and linear ranges, for various sensing platforms. Finally, the write-up will discuss advanced sensor technology and address the improvements made on electrochemical sensors and biosensors for pesticide detection, which will be important in future studies on pesticide determination.